Impact of Social Safety Net Programme : allowances for old age, husband deserted destitute women and the widow : a study on seven union parishads from seven divisions of Bangladesh - Motahar Hossain, Md.; Abul Hasem, Md.; National Institute of Local Government (Bangladesh) (Dhaka : National Institute of Local Government, 2014)
Study on the impact of Social Safety Net Programme for the welfare of old and destitute women in rural Bangaldesh.
Includes bibliographical references (pages 75-77).
Keywords: Social Safety Net Programs -- Bangladesh; Social security -- Bangladesh; Old age assistance -- Government policy -- Bangladesh; Poor women -- Government policy -- Bangladesh; Widowers -- Government policy -- Bangladesh